Elasto-plastic constitutive interface model for an axisymmetric contact problem - Buczkowski, Ryszard; Kleiber, Michał (Computer Assisted Methods in Engineering and Science, 1994)
A solution to plane and axisymmetric elasto-plastic contact problem with linear hardening of contacting bodies, taking into account microstructural features of the contact zone is presented. A new quadratic-isoparametric contact element involving the irreversible nature of friction is developed. An incremental constitutive friction law, analogous to the classical theory of plasticity, is used. Several numerical examples are considered. The influence of parameters defining the contact stiffness interface on the distribution of displacements and stresses on the contact surface is discussed.